A community-based study to estimate the burden and determinants of risk of developing obstructive sleep apnea among adults in an area of North India - Garima Sangwan; Nitika Sharma; Rajesh Garg; Sangeeta Dureja (Indian Journal of Community and Family Medicine)
Introduction: Obstructive sleep apnea (OSA) is an often underestimated sleep disorder that poses significant health risks among adults worldwide. This community-based cross-sectional study was undertaken to estimate the burden of risk of developing OSA in the population and study the factors making people susceptible to developing OSA. Material and Methods: The community-based cross-sectional study was conducted in the field practice areas of the Department of Community Medicine, Kalpana Chawla Government Medical College, Karnal, among 310 adults using Berlin Questionnaire that assesses an individual’s risk of developing OSA based on questions related to symptoms, anthropometry, and hypertension. Data were analyzed using univariate and multivariate regression analyses at a significance level of p-value <0.005. Results: The study included a total of 310 participants, with a mean age of 47.5 years (SD ± 13.6) and a range from 21 to 82 years. Among 310 participants, 21% were at high risk of developing OSA. Overall, in multivariate analysis, history of chronic disease (adjusted odds ratio = 14.29, 95% confidence interval: 5.26–16.67, p < 0.001) age, and body mass index (BMI), emerged as significant predictors of the risk of OSA in the target population. Conclusion: Among the participants, 21% were at high risk for OSA, with chronic disease history, age, and BMI emerging as significant predictors in multivariate analysis. Understanding the factors making people susceptible to develop OSA would give an opportunity to educate the people about its prevention and would contribute in formulating a preventive and screening strategy for OSA, which is currently not in place.